HL Influences Diabetes Education Preferences of Parents of Children with Diabetes - Parry, Nicola (MD Conference Express, 2014)
This article presents the results of a study showing that parents of children with type 1 diabetes mellitus prefer a learner-driven diabetes curriculum that is geared toward their health literacy (HL) needs.